2014
DOI: 10.1016/j.cemconres.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term creep properties of cementitious materials: Comparing microindentation testing with macroscopic uniaxial compressive testing

Abstract: This study is dedicated to comparing minutes-long microindentation creep experiments on cement paste with years-long macroscopic creep experiments on concrete and months-long macroscopic creep experiments on cement paste. For all experiments, after a transient period the creep function was well captured by a logarithmic function of time, the amplitude of which is governed by a so-called creep modulus. The non-logarithmic transient periods lasted for days at the macroscopic scale, but only for seconds at the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“… SiO 2 / Na 2 O ‐mole ratio and equivalent Na 2 O ‐content of the applied activator in the alkali‐activated slag ( AAS )‐concrete in comparison to literature references …”
Section: Precursor Materials and Concrete Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“… SiO 2 / Na 2 O ‐mole ratio and equivalent Na 2 O ‐content of the applied activator in the alkali‐activated slag ( AAS )‐concrete in comparison to literature references …”
Section: Precursor Materials and Concrete Compositionmentioning
confidence: 99%
“…From these investigations it can be concluded that the lower the Ca/Si‐ratio is, the lower is the contact creep modulus of C‐S‐H. In References and the contact creep moduli of C‐S‐H and cement pastes obtained from nano‐/microindentaion experiments were compared with long‐term uniaxial creep experiments performed at concrete samples. It was found that the creep of concrete increases with the decrease of contact creep moduli of C‐S‐H or cement pastes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indentation is an experimental technique to measure the mechanical properties of small volumes of materials, and in particular their creep properties [37]. Both nanoindentation [11] and microindentation [22] make it possible to characterize the long-term kinetics of logarithmic creep of cement-based materials, and provide results that are quantitatively consistent with the longterm kinetics of logarithmic creep characterized by macroscopic testing. Such consistency is surprising, because indentation experiments only last for a few minutes, while the characteristic time of logarithmic creep characterized by macroscopic testing is much longer, rather on the order of the day ( figure 6 or figure 8).…”
Section: (C) Measurement Of Creep Properties By Indentationmentioning
confidence: 99%
“…The macroscopic uniaxial compressions are those respecting the criteria enumerated in §3; data are from[30][31][32][33][34][38][39][40][41][42][43][44][45][46][47][48]; each data point corresponds to an average performed on all experiments on 1 mix design, independent of the load level or of the age at loading. Berkovich indentations at 2 and 100 mN and cube corner indentations at 0.5 mN are from[49], and Berkovich indentations at 20 N are from[22]; each data point corresponds to an average performed on all indentations performed on the hydrates of 1 mix design; the applied macroscopic stress is equal to the average of the measured indentation hardnesses. (Online version in colour.…”
mentioning
confidence: 99%